KONSEP PEMBELIAN KOMPULSIF: SEBUAH KETERPAKSAAN - A - Alfitman; Basu Swastha Dharmmesta; Bayu Aji Aritejo (MIX: JURNAL ILMIAH MANAJEMEN, 2021)
Until 2020, there is no consensus among researchers about the actual compulsive buying concept is. There are many different compulsive buying concepts in the scientific literature (Ridgway et al., 2008; Goldsmith et al., 2015).  Consequently, it is difficult for marketers to implement it in marketing decision making. This study aims to clarify it by categorizing any existing compulsive buying concepts in scientific literature and offer one of which for the best explanation. Based on a literature study, we collected data from any scientific research in any discipline. By using bibliometric analysis, the concept of compulsive buying can categorize it into three categories: compulsive buying as a disease, as a bad habit or "a want" or consumer culture, and as a force. Among the compulsive buying categories, this study has offered the compulsive buying as a force to be the best concept for compulsive buying explanation. The idea can clarify the concept of compulsive buying to be better because it can differentiate compulsive buying from similar concepts such as addiction, impulsive buying, and obsessive-compulsive disorder.